Customizing an all-in-one polydimethylsiloxane-based electroanalytical platform using a 3D-pen templated channel - Silva do Carmo, Jéssica da; Roveda, Liriana Mara; Rodrigues, Raphael; de Carvalho, Cláudio Teodoro; Trindade, Magno Aparecido Gonçalves [UNESP] (Wiley, 2024)
The combination of 3D-printing technology and microfluidics has garnered widespread interest for creating new designs and has opened a large window for creativity. However, some laboratories do not have the necessary technology to explore this potential advantage. In this paper, we demonstrate how to explore target technologies to fabricate a single version of a polydimethylsiloxane (PDMS)-based electroanalytical platform using a low-cost protocol and disposable materials. This protocol is cost-effective in terms of equipment and materials, allowing for the creation of a circular channel, a T-junction system, and two designs of electrochemical detectors customized onto a single platform. The interesting new device has some important characteristics, such as fabrication following green and sustainable protocols. Additionally, it can address the limitations associated with flow-based analysis, for which the classical three-electrode configuration is inadequate. It has also demonstrated the feasibility of using the device in analytical applications for the determination of salicylic acid in commercial dermocosmetic samples, including aqueous samples.
Keywords: 3D-based channel; disposable materials; integrated electrochemical detector; lab-made devices